IMPLEMENTASI VIDEOGRAFI DALAM DIGITAL CAMPAIGN CREATIVE VIDEO INTERVIEW TSP SQUAD - Nursyam, Muhammad; Santoso, Hudi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to explain the implementation of videography in the digital campaign by TSP Squad using a creative video interview format with a descriptive qualitative approach. Data were collected through observation, active participation in the production process, and relevant literature review. The results show that videography implementation through visual storytelling, composition, lighting, and shooting techniques contributes to the production of informative and engaging video content. The production process, which includes pre-production, production, and post-production stages, also plays a role in shaping the final output in line with the objectives of the digital campaign.